GA Houses 182. - Radic, Smiljan; Ishigami, Junya; Lehmann, Cristián Izquierdo; Hata, Tomohiro (Tokyo : A.D.A. Edita, 2022)
Smiljan Radic - Prism House + Terrace Room ; Junya Ishigami - House & Restaurant ; Cristián Izquierdo Lehmann - House in Matanzas ; Cristián Izquierdo Lehmann - San Crecente Housing Ensemble ; Tomohiro Hata - House in Minoh ; Yo Shimada - House in Shoji ; Mathias Klotz - Studio House 2.0 ; Mathias Klotz - Patio House ; Keitaro Muto - OOSU
boek